Kredibilitas dan Daya Tarik Pustakawan Sebagai Komunikator Terhadap Kepuasan dan Loyalitas Pemustaka - Nurasmi; Nurjanah; Zurkarnain (Perpustakaan Universitas Riau, 2021)
Good library management must be implemented. In order for management to be carried out properly, a credible and competent librarian is needed in carrying out their duties. This study aims to examine the effect of librarian credibility and librarian attractiveness on visitor satisfaction and loyalty. The research uses a quantitative approach. The analytical method used is Structural Equation Modeling (SEM). Statistical analysis tools used are PSPP and LISREL application. The number of research samples is 200 people. The final analysis used Confirmatory Factor Analysis (CFA). The results showed that the credibility of the librarian has a significant effect on visitor satisfaction (T value = 4.34), the attractiveness of the librarian has a significant effect on visitor satisfaction (T = 3.302). The librarian's credibility does not directly have a significant effect on customer loyalty (T-values = 1.22) but indirectly significantly (T-values = 2.129), the attractiveness of librarians does not directly significantly affect customer satisfaction (T-values). = 1.07), but through intervention (indirectly the attractiveness of librarians has a significant effect on customer loyalty (T value = 2.354), customer satisfaction also has a significant effect on customer loyalty (T value = 2.42). significant direct effect on visitor satisfaction and indirectly on the loyalty of library users at the Riau University Library.